Bio Electro Magnetic Energy Regulation (BEMER) therapy in myofascial pain dysfunction syndrome: A preliminary study - Alekhya Kanaparthi; Satya Prakash Reddy Kesary; Chada Pujita; Hema Gopalaiah (Journal of Oral Biology and Craniofacial Research)
Background: Myofacial pain dysfunction syndrome (MPDS) is of the commonest form of orofacial pain encountered in the clinics. Though, many therapies have been suggested in the recent past, still the management of this condition remains a therapeutic problem. The search for newer, relatively safe and effective long term approach lead to the use of magnetic stimulation in pain modulation. Bio Electro Magnetic Energy Regulation is one such modality that has been studied in the musculoskeletal disorders. However, no studies in this regard have been explored in orofacial region. Objectives: The objective of the present study was to evaluate the efficacy of BEMER therapy as an adjuvant to relieve pain in myofascial pain dysfunction syndrome. Materials and methods: The present randomized comparative study was on 40 patients who were diagnosed with Myofacial pain dysfunction syndrome(MPDS). They were grouped into two groups of 20 each. Group 1 patients were administered analgesic + muscle relaxants & Group 2 was receiving both analgesic + muscle relaxants with BEMER therapy. All the patients were evaluated for pain relief on visual analog scale (VAS) and the mouth opening (MO)was measured using digital vernier callipers. Results: The group 2 showed a significant improvement in the symptoms even after 2 months follow up. In group 2 the mean mouth opening was 45.60 ± 3.648(P < 0.05) and 45.50 ± 3.663(P < 0.05); the Mean VAS Score was 3.10 ± 0.912 and 2.90 ± 0.968(P < 0.05) after one month and after two months respectively. The independent t-test, was used for inferential statistics. Conclusion: It can be concluded from this study that Combined therapy proved to be more effective in providing long term symptomatic relief compared to conventional pharmacological therapy. BEMER as an adjuvant therapeutic modality proved to be beneficial in the management of MPDS.